2019
DOI: 10.20491/isarder.2019.732
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Conspicuous Consumption in Social Media on Purchasing Intentions

Abstract: With the rapid increase in the use of social media in the last decade, the conspicuous consumption lifestyle within society has been now transferred to the social media. Along with the changing culture of consumption, the consumer who witnesses such portrayals on social media aspires to and desires the same products and services. Having regard to this situation, this study examines the impact of the conspicuous consumption trend in social media on purchasing intentions. Accordingly, the study aims to discover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Attitudes toward social media advertising positively affect millennial buying interest, and peer communication also significantly influences millennial buying (Pandey, Sahu, & Dash, 2018). Efendiȯğlu (2019), in his research, also obtained results whereby social media is used as a conspicuous consumption channel that influences purchase intention and has a positive impact. In addition, it was found that social media marketing significantly influences purchase intention and brand loyalty (Laksamana, 2018).…”
Section: Purchase Intentionmentioning
confidence: 85%
See 1 more Smart Citation
“…Attitudes toward social media advertising positively affect millennial buying interest, and peer communication also significantly influences millennial buying (Pandey, Sahu, & Dash, 2018). Efendiȯğlu (2019), in his research, also obtained results whereby social media is used as a conspicuous consumption channel that influences purchase intention and has a positive impact. In addition, it was found that social media marketing significantly influences purchase intention and brand loyalty (Laksamana, 2018).…”
Section: Purchase Intentionmentioning
confidence: 85%
“…Bogor, Depok, Tangerang, Bekasi), and knew promotions carried out through the Bittersweet by Najla TikTok account. Efendiȯğlu (2019), in his research, also obtained results whereby social media is used as a conspicuous consumption channel that influences purchase intention and has a positive impact. In addition, it was found that social media marketing significantly influences purchase intention and brand loyalty (Laksamana, 2018).…”
Section: Social Media Marketing Purchase Intentionmentioning
confidence: 87%
“…al (2017) state that technology can increase the desire to consume. So, an increase in social media use could impact status-related consumerism concepts like conspicuous consumption (Efendioğlu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…state that technology can increase the desire to consume. So, an increase in social media use could impact status-related consumerism concepts like conspicuous consumption (Efendioğlu, 2019).…”
Section: Introductionmentioning
confidence: 99%